INTERRELATION BETWEEN TOURIST RISK PERCEPTION AND DESTINATION IMAGE AND REVISIT INTENTION EAST LOMBOK POST EARTHQUAKE - Ni Wayan Marsha Satyarini; Tamjuddin Tamjuddin; Ramdhan Kurniawan (Universitas Terbuka, 2019)
This research developed of tourist risk perception and destination image and revisit intention. Theresearch also focused how tourists are influenced by natural disasters and provides empirical evidenceto predict the hypothesis models. The results of a study of 230 of local and international tourists visit toEast Lombok post the earthquake. This study examining:(1) the effect of risk perception and destinationimage (2) the effect of destination image and revisit intention (3) the effect of risk perception and revisitintention post natural disaster. Results as expected, all results had positive and significant relationbetween variables. This research used SEM-AMOS as analysis method.